Comparison of Locking and Frag-Loc Screws for Fixation of Die-Punch Fragments - Kanazawa, Takaaki (J Wrist Surg, 2018)
Background  The Frag-Loc (FL) compression screw system was designed to stabilize dorsally displaced intra-articular dorsoulnar (die-punch) fragments in distal radius fractures. Purpose  Comparison of the biomechanical properties of fixation of the die-punch fragment (stiffness, ultimate strength, and displacement ratio of the fragment), using the FL and traditional locking screw (LS), and using simulated distal radial fractures in cadaveric specimens under axial compressive loading. Both screws were used with a volar locking plate (VLP). Materials and Methods  Eight matched pairs of formalin-fixed cadaveric specimens of the radius were used to simulate distal radius fractures with die-punch fragments. The die-punch fragment was fixed using VLP with either FL group or LS group. Biomechanical properties for the two fixation systems were evaluated under axial compression loading, applied at a constant rate of 0.5 mm/min until failure. Load data were recorded and the ultimate strength and change in the gap between the die-punch and proximal fragments measured, with the displacement ratio calculated by dividing the value of the gap before loading by the gap after loading. Failure was defined as 10 mm or more of fragment displacement, or screw failure. Results  There were no differences in ultimate strength ( p  = 0.47) or stiffness ( p  = 0.061) between the two fragment fixation systems. However, the displacement ratio was lower for the FL than for the LS system ( p  = 0.049). Conclusion  Compared with LS, the FL system lowers the displacement of die-punch fragments under compressive loading. Clinical Relevance  The FL system is effective for the treatment of distal radius fractures with die-punch fragments.